Involvement of tumor-associated macrophage activation in vitro during development of a novel mantle cell lymphoma cell line, PF-1, derived from a typical patient with relapsed disease. Issue 1 (January 2015) - Pham, Lan V.; Vang, Muychi T.; Tamayo, Archito T.; Lu, Gary; Challagundla, Pramoda; Jorgensen, Jeffrey L.; Rollo, Alex A.; Ou, Zhishuo; Zhang, Liang; Wang, Michael; Ford, Richard J.
Abstract Human mantle cell lymphoma (MCL) cell lines are scarce and have been only sporadically described and validated, and only a few have been thoroughly molecularly or genetically characterized. We describe here the successful establishment of a new MCL line, PF-1, with typical MCL characteristics. Culturing primary MCL cells in vitro initially gave rise to an essential generative microenvironment "niche" involving macrophages required for MCL growth, and eventually produced the PF-1 MCL cell line. Our analysis revealed that PF-1 is morphologically and genotypically nearly identical to the original tumor cells. The PF-1 MCL cell line that we have developed will be useful for in vitro and in vivo studies of MCL pathogenesis and therapeutics.